Evaluation of Jute (Corchorus olitorius): a naturalistic fiber as nesting material for home cage enrichment in laboratory mice (Journal of Laboratory Animal Science, 2025)
Environmental enrichment of home cages has a positive effect on animal wellbeing as well as the quality of research.  Laboratory mice although separated from their wild ancestors still show natural instincts. It is interesting to observe  whether the laboratory mice build a better complex nest with the naturalistic material in comparison to commercially  available, processed or commonly used nesting material. Therefore, we have tested the nest-building characteristics of  the laboratory mice provided with crinkled paper (P), jute (Corchorus olitorius) (J), coconut coir (C) or, jute-coir blend  (JC). We observed that nest of mice with “J” scored higher than “JC” and “P”. Mice preferred naturalistic fibrous material  above commercially available crinkled paper. It built a better stable nest using jute and preferred to stay in jute for most  of the time (mainly 70% in night time and 42% in daytime) and showed very less preference for crinkled paper. The nest  made out of jute was also proved to be stable for up to 14 days, suggesting its use in experiments that warrant the mice to  be kept undisturbed for two weeks. Mice did not show any undesirable behaviour due to any of the nesting material used  in this experiment. Jute is of low cost, easy to handle, and can be used as environmental enrichment for laboratory mice.
Keywords: Nesting material; enrichment; laboratory mouse; jute; coir